THE KANSAS DEPARTMENT OF HEALTH AND ENVIRONMENT (KDHE) PHYSICAL ACTIVITY AND NUTRITION PROGRAM: FIELD EXPERIENCE REPORT - Ndlela, Arlerta Samkelisiwe (My University, 2013)
This report presents a detailed field experience undertaken for 240 hours with the Kansas State Department of Health and Environment (KDHE), Physical Activity and Nutrition (PAN) program. The mission of the Physical Activity and Nutrition program is to increase the number of Kansas residents who have the knowledge, motivation and opportunity to make lifestyle choices that promote healthy eating and increased physical activity through state level leadership and coordination that reaches into communities across the state. Work on health policy development and implementation through strategies directed to prevent obesity and other chronic disease and promotion of healthy food choices will be discussed. Completed projects include the development of an issue paper, data management for the Senior Farmers Market Nutrition Program (SFMNP), a program designed to increase the consumption of fruit and vegetables for low-income older adult population; and the Rapid Market Assessment, an evaluation of the contribution of the Capitol Mid-Week Farmers Market designed to increase consumption of fruit and vegetable by downtown employees while contributing to the local economy. The experience of being the Physical Activity and Nutrition intern at the Kansas State Department of Health and Environment deepened my understanding of policy development and implementation processes for the prevention of obesity and other chronic diseases through evidence based strategies, in collaboration with other government departments and private organizations.
Keywords: Physical activity and nutrition; Public health; Public Health (0573)